21st Century Medical Education in University of Malaya21st Century Medical Education in University of Malaya - Tan, C.P.L.; Blitz, J.J. (Faculty of Medicine, University of Malaya, 2008)
What does this term medical education conjure up? Does it refer to the teaching and learning of medicine and therefore relates to students and the curriculum? Does it refer to the process of teaching and therefore relates to teachers? Perhaps it is both, since teaching and learning go hand in hand.